Perceived victimization as the mechanism underlying the relationship between work stressors and counterproductive work behaviors. Issue 5 (19th October 2016) - An, Mihyang; Boyajian, Melanie E.; O'Brien, Kimberly E.
ABSTRACT: Employees who report workplace stressors are more likely to engage in counterproductive work behavior (CWB). However, the specific mechanisms that underlie these relationships are not well understood. This study utilizes a moderated-mediation model to examine perceived victimization as the mediator between work stressors and CWB. This model is investigated using data from 207 matched subordinate–supervisor pairs via a multiphasic data collection, with results revealing that work stressors (workload, organizational constraints, and interpersonal conflict) are related to CWB and that these relationships are mediated by perceived victimization by workplace aggression for people with more hostile attributional styles. The implications are that varying reasons for engaging in CWB may exist, based on the employee's interpretation of events.